Design of Prototype Early Warning System for Ship Gas Leakage and Fire Using MQ-6 Sensor and Arduino Uno Microcontroller - Chandra, Yudi Irawan; Sjafrina, Fitri; Irawati, Diyah Ruri; Riastuti, Marti (Innovation in Research of Informatics (Innovatics), 2025)
Maritime transportation is vital for global trade but faces risks from gas leaks and fires, which can endanger ships and crews. Many small and medium-sized vessels lack effective systems to detect hazardous gases early, raising the chance of accidents. This study focuses on developing a prototype early warning system to detect gas leaks and fires on ships using an MQ-6 sensor and an Arduino Uno microcontroller. The goal is to provide a low-cost, real-time monitoring solution to improve maritime safety. The research follows a hardware prototyping and software development process using a waterfall approach, including requirement analysis, system design, implementation, testing, and deployment. The MQ-6 sensor identifies flammable gases like LPG and butane, while the Arduino Uno processes the sensor data and triggers alarms when gas levels become dangerous. The prototype was tested in a simulated ship environment to assess its sensitivity, response time, and reliability. Test results show that the system detects gas concentrations above safe limits within 3 to 5 seconds, activating visual and audio alarms quickly. The device also operates continuously with low power consumption, making it suitable for long-term use on ships. The study shows that this prototype can serve as an affordable and reliable additional safety device for maritime settings. This research supports efforts to improve ship safety systems by offering a practical way to reduce risks from gas leaks and fires. The system’s simplicity and effectiveness make it a promising option for enhancing onboard hazard detection.